2021
DOI: 10.34005/kinerja.v3i02.1574
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Penghindaran Pajak Dengan Komisaris Independen Sebagai Pemoderasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019

Abstract: The study aimed to test the effect of leverage, company size, inventory intensity and liquidity on tax avoidance.In addition, this study also aims to test the influence of independent commissioners who act as moderation. This study was conducted by moderate regression analysis method with sample selection method that is purposive sampling with a sample of 21 manufacturing sector companies during the period 2015-2019.The results showed that leverage positively affects tax avoidance and liquidity negatively affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
1
4
0
Order By: Relevance
“…This finding is in line with the previous research conducted by (Muliawati & Karyada, 2020;A. Octaviani & Trishananto, 2022;Pitaloka & Merkusiwati, 2019;Silaban, 2020;Wicaksana et al, 2021) who stated that leverage is positively and significantly affects tax avoidance.…”
Section: Effect Of Leverage On Tax Avoidancesupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in line with the previous research conducted by (Muliawati & Karyada, 2020;A. Octaviani & Trishananto, 2022;Pitaloka & Merkusiwati, 2019;Silaban, 2020;Wicaksana et al, 2021) who stated that leverage is positively and significantly affects tax avoidance.…”
Section: Effect Of Leverage On Tax Avoidancesupporting
confidence: 92%
“…The results from prior researchers by (A. Octaviani & Trishananto, 2022;Wicaksana et al, 2021) found that Independent Commissioners is able to moderate the negative effect of leverage on tax avoidance. Based on the framework of thinking above, the hypothesis proposed in this research is stated as follows:…”
Section: The Relationship Among Leverage Tax Avoidance and Independen...mentioning
confidence: 92%
See 1 more Smart Citation
“…This sales growth uses sales at the end of the period with the previous year's sales based on Oktamawati (2017), Prastika (2021), and Winda & Nariman (2021), who obtained the following formula: IDX's regulations regarding stock requirements on the Indonesia Stock Exchange explained that the number of independent commissioners assigned as a control to the company must be at least 30 percent of all members of the board of commissioners (BEI, n.d.). The following is the formula for determining the number of independent commissioners from Kusufiyah & Anggraini (2019), Syadeli (2021), andWicaksana et al (2021).…”
Section: ( )mentioning
confidence: 99%
“…It is more relevant because sales growth will show excess asset capacity and requirement funding in the form of debt with a large interest expense, reducing the company's income tax (Tristianto & Oktaviani, 2016). Prastika (2021), Supriyanto (2021), andWicaksana et al (2021) employed the Effective Tax Rate (ETR), while Badoa (2020) and Rani et al (2021) used the Cash Effective Tax Rate (CETR) for tax avoidance proxy. However, this research is more relevant to using the Abnormal Book Tax Difference (ABTD) for tax avoidance proxy because when it shows the difference between fiscal profit and accounting profit, there is a gap in accounting earnings management that is bigger and the same in the reporting period (Falbo & Firmansyah, 2021).…”
Section: Introductionmentioning
confidence: 99%